Public Theology - Höhne, Florian (SysLex, 2026)
"CSU is playing tricks with a symbol of faith". This is the title of a guest article published on April 2018 by the Munich emeritus professor of theology Friedrich Wilhelm Graf in the Süddeutsche Zeitung newspaper. Graf comments on the Bavarian Prime Minister Markus Söder’s decision to have crosses hung up in Bavarian government buildings. He recounts the history of the symbol of the cross, clarifies its meaning within Christian religious culture, and reaches the conclusion that the state government is misusing the cross "for very superficial political purposes." The example of Graf’s article shows how theology can participate in a public debate on a current political issue in a comprehensible, relevant, and stimulating manner. This is precisely what public theology reflects upon and strives for: the public relevance of theological discourse and the theological engagement with pressing issues in the public sphere. Public theology reflects on how theology is public. As such, public theology is not a new theological discipline alongside church history, biblical studies, practical, and systematic theology. Nor can it be reduced to ethics. Rather, it emphasizes the cross-sectional (Querschnittsaufgabe) task of theology to reflect upon its public character. Public theology also does not offer a political agenda for the Church or represent a new school of theological thought. It is more so a discourse in which different perspectives are brought to bear on questions of public relevance.